Computing new solutions of algebro-geometric equation using the discrete inverse Sumudu transform - Adem Kılıçman; Rathinavel Silambarasan (Advances in Difference Equations, 2018)
Abstract The discrete inverse Sumudu transform method is designed to solve ordinary differential equations and tested for an algebro-geometric equation. The two new sets of exact analytical and complex solutions are gotten through a discrete inverse Sumudu transform, and Maple complex graphs are drawn to show the new solution simulations in the complex plane which are compared to the existing solutions. The list of inverse Sumudu transforms is added in the sequel to strengthen the study.